The formation of inclusion complex of phenobarbital with hydroxypropyl-Î²-cyclodextrine - Isadiartuti, Dewi; ., Suwaldi (INDONESIAN JOURNAL OF PHARMACY, 2005)
Phenobarbital, a hypnotic and sedative agent, was found to form inclusion complex with hydroxypropyl-Î²-cyclodextrine at 1:1 molar ratio. The formation of inclusion complex in the solution was detected due to the increased solubility of phenobarbital and in the solid was confirmed by differential scanning calorimetry, X-Ray diffractometry, and infrared spectroscopy.In the solid, inclusion complex was prepared by freezed drying method. The inclusion complex formed was characterized, compared with phenobarbital, hydroxypropyl-Î²-cyclodextrine, and the physical mixture of phenobarbital and hydroxypropyl-Î²-cyclodextrine.Analyses using DSC and X-ray diffractometry showed that phenobarbital formed inclusion complex with hydroxypropyl-Î²-cyclodextrine.Key words : phenobarbital, hydroxypropyl-Î²-cyclodextrine, inclusion complex